Is pitolisant safe for clinical use? A retrospective pharmacovigilance study focus on the post‐marketing safety - Cheng Jiang; Jiancheng Qian; Xin Jiang; Shuohan Zhang; Junxian Zheng; Hongwei Wang (Wiley, 2024)
Abstract Pitolisant, a novel histamine H3‐receptor antagonist, holds significant promise for treating narcolepsy. However, a petition, which highlighted that pitolisant was associated with deaths during clinical trials, has propelled it into the spotlight of widespread societal attention on April 3, 2023. Till now, the clinical safety of pitolisant remains a heatedly debated topic. This study aimed to offer a comprehensive assessment of the safety profile of pitolisant in real‐world clinical settings. Adverse event reports where pitolisant was the primary suspect drug were extracted from the FDA Adverse Event Reporting System database. The clinical characteristics and concomitant drugs of the pitolisant‐associated adverse events were analyzed. The potential adverse event signals of pitolisant were explored using four disproportionality analysis methods. Furthermore, the difference in pitolisant‐associated adverse event signals was investigated concerning sex, age, weight, and dose. A total of 526 reports and 1695 adverse events with pitolisant as the primary suspected drug were identified. The most significant adverse event signals were generally mild and of short duration. The concomitant drugs of pitolisant were highly intricate, mainly included drugs for treating narcolepsy as well as antidepressants. Seven new significant adverse event signals emerged. The safety profile of pitolisant exhibited no significant differences across age and dose groups, although slight variations were observed in relation to sex and weight. The findings from reports of death and life‐threatening outcomes underscore the importance of enhanced monitoring for cardiac and respiratory adverse reactions when utilizing pitolisant. This study provided a broader understanding of the safety profile of pitolisant.